2003
DOI: 10.1002/adma.200304623
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant‐Assisted Growth of Novel PbS Dendritic Nanostructures via Facile Hydrothermal Process

Abstract: lated and exfoliated PMMA and PS±clay nanocomposites foams were prepared using supercritical CO 2 as the foaming agent. Presence of a small amount of clay nanoparticles greatly reduces foam cell size and increases the cell density. Exfoliated nanocomposites yield foams with the smallest cell size and the highest cell density. Cell morphology can be furthered manipulated by adjustment of polymer±clay surface±CO 2 interaction and foaming conditions to achieve microcellular and submicrocellular foams. The high nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
204
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(217 citation statements)
references
References 67 publications
5
204
2
Order By: Relevance
“…Compared to it, the hydrothermal method is low cost and convenient for operating, what has been used for synthesis of many thermoelectric materials such as PbTe [12,13], Bi2Te3 [14][15][16] and CoSb3 [17]. As far as we know, there is little reported on the thermoelectric performance of hydrothermal synthesis of PbS [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to it, the hydrothermal method is low cost and convenient for operating, what has been used for synthesis of many thermoelectric materials such as PbTe [12,13], Bi2Te3 [14][15][16] and CoSb3 [17]. As far as we know, there is little reported on the thermoelectric performance of hydrothermal synthesis of PbS [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…From the SEM and TEM, we know it could restrict longitudinal growth effectively. Many papers had reported the fabrication nanostructures by using CTAB as a surfactant [8][9][10][11]. In this system, a water-in-oil (w/o) microemulsion is a transparent and isotropic liquid medium with nanosized water pools dispersed in a continuous phase and stabilized by CTAB and n-butanol at the water/oil interface.…”
Section: +mentioning
confidence: 99%
“…Microemulsion-mediated hydrothermal method has been extensively used for fabricating nanostructures materials [8][9][10][11][12]. In this method, the surfactant has been used as template for controlling the size and shape of nanocrystals [13].…”
Section: Introductionmentioning
confidence: 99%
“…Prashar et al (2010) have reported low-temperature synthesis of gadolinium monosulfide (GdS) nanoparticles and their pathogen capture efficiency. Nanosized materials have a larger surface area and the quantum mechanical effects such as 'quantum size effect' begins to play a significant role (Shi et al 2003;Zhang et al 2005;Kuang et al 2003;Kim et al 2004;Markovich et al 1999). Since properties of nanoparticles are highly dependent on their structure, size, and morphology, changes in concentration, temperature, and solvents are found to play a critical role in controlling the size-dependent properties.…”
Section: Introductionmentioning
confidence: 99%